Flags of subalgebras in contracted Lie algebras - Popovych, D. R. (Reports of the National Academy of Sciences of Ukraine, 2021)
We prove a theorem that describes the behavior of subalgebra flags of Lie algebras under contractions and can be applied as a new criterion for the non-existence of contractions. A weaker version of the theorem is ob tained for flags of subspaces. Using the theorem, we prove the non-existence of contractions for a number of pairs of sixdimensional nilpotent real Lie algebras, for which the earlier known criteria do not work.